Impact of Instructional Assessment on Elementary Children's Achievement - Meisels, Samuel J. (Education Policy Analysis Archives, 2003)
This study examined the trajectory of change in scores on the Iowa Tests of Basic Skills (ITBS) of low-income, urban, third and fourth graders who had been enrolled in classrooms where the Work Sampling System (WSS), a curriculum-embedded performance assessment, was used for at least three years. The ITBS scores of children exposed to WSS were compared with those of students in a group of non-WSS contrast schools that were matched by race, income, mobility, school size, and number of parents in the home and to a comparison group of all other students in the school district.